Family management of pediatric cancer: Links with parenting satisfaction and psychological distress - Salvador, Ágata (2022)
Research has long acknowledged the disruptions posed by pediatric cancer diagnosis and treatment to family life. Nonetheless, the mechanisms through which the family response influences parents’ mental health in this adverse context are not fully understood. The main goal of the present study was to examine the direct and indirect links, via parenting satisfaction, between family condition management and psychological distress of parents of children with cancer. Participants were 201 parents (86.6% mothers) of children/adolescents diagnosed with cancer who completed selfreport questionnaires assessing family condition management (family life difficulty and parental mutuality), parenting satisfaction and psychological distress (anxiety and depression). Structural equation modeling was used to test the proposed mediation model. The results showed that parenting satisfaction mediated the association between both the family condition management dimensions (family life difficulty and parental mutuality) and depression. Specifically, greater family life difficulties and lower parental mutuality were associated with lower parenting satisfaction, which, in turn, was associated with higher levels of depression. Additionally, greater family life difficulties and lower parental mutuality were directly linked to higher levels of anxiety. Multigroup analyses suggested that the model was valid across patient age groups (children vs. adolescents) and treatment status (on vs. off-treatment). These findings reinforce the need for family- and parent-based interventions in the pediatric oncology field. Interventions that target families’ difficulties and promote their resources are likely to foster parenting satisfaction and psychological adjustment.